-10+6r-8=-r+10

Simple and best practice solution for -10+6r-8=-r+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+6r-8=-r+10 equation:



-10+6r-8=-r+10
We move all terms to the left:
-10+6r-8-(-r+10)=0
We add all the numbers together, and all the variables
6r-(-1r+10)-10-8=0
We add all the numbers together, and all the variables
6r-(-1r+10)-18=0
We get rid of parentheses
6r+1r-10-18=0
We add all the numbers together, and all the variables
7r-28=0
We move all terms containing r to the left, all other terms to the right
7r=28
r=28/7
r=4

You can always share this solution

See similar equations:

| (5x+1)/(x-1)=0 | | 5(n-2.95)=47.75 | | Y=-5x(-1)+2 | | 6x+29=95 | | 3x+x=496 | | a/18=6.8 | | -3-8w=-9w | | -1-2p=-4p+9 | | 71=14-2x | | x+30x/100=45.5 | | -9c-6=-10c | | 11+6x-14=3/5(15-5) | | -3m-10=-4m | | -4d=10-5d | | -9s+5=-10s | | 6.25=0.75x+250 | | 3r-10=2r | | 2x+2=63 | | 0=-16t^2+221 | | 0.12y-1.6(y-2)=6.8-1.28 | | -4j+7j-16j+-13j+19=-7 | | -13x+3(2x-3)=-15-6x | | 5b-4b+3b+2b-3b=6 | | y2=38 | | 13r-2r+5r-15r=5 | | 63+7k=8k | | -88=-7+11r | | -18h+-8h+15h+18h+-8h=-15 | | 5/3x=5x/3 | | q+18q-18q-3q+q+-10=-9 | | 9z-3+8z-8+72=180 | | 50x^2-60x-7=0 | | 9.6(x=3.75)=-28.8 | | 6y-12y=-16-20 | | 2b-b-b+3b+2=11 | | X=(2y)-49000 | | 4c-3c-7c+12=0 | | 2x-37=10 | | -10t+8t-9t=11 | | 14k+6k-19=1 | | 1/3(5x+6)(x+5)=3 | | 5n=10(2) | | 12q-6q+4q+3q-12q=14 | | 52x+12x=1012+92x | | 10r+4r-10r-r=18 | | 11+b=2b+2 | | 5^2-24x-5=0 | | 11y+4y-14y=12 | | 3x-3x+6=6 | | 5x+12=2x+65x+12=2x+6. | | 24=120x | | -10w+10w+20w?-3w+-20w=-18 | | z/18=8 | | 60x-0.4x^2+5x+14=0 | | 60=10a/2 | | 21x-13-14x-8=180 | | -6-(-41)*8=x | | 3y+1=52 | | 7x+5x-17=34-5x | | 2v+4v+v-6v=5 | | c+c+2c-4c+c=17 | | 12x-18=4x+6 | | 14x-19=6x+29 | | 2(x-1)+3-2=7 | | 20b?16b+-14b=-10 |

Equations solver categories